KESEPADANAN PADA PENERJEMAHAN KATA BERMUATAN BUDAYA JEPANG KE DALAM BAHASA INDONESIA : Studi Kasus dalam Novel Botchan Karya Natsume Soseki dan Terjemahannya Botchan Si Anak Bengal oleh Jonjon Johana - Dewi Puspitasari; Eka Marthanty Indah Lestari; Nadya Inda Syartanti (IZUMI, 2014)
There are many ways that could be done to introduce unique culture of a country to the international world; one of them is through translation works.  This can be seen through Japanese literary works, which are translated into other languages.  Botchan is one of the best literary works from Natsume Soseki that was translated into several languages, including Indonesian language, with the title of the translation Botchan Si Anak Bengal by Jonjon Johana. This novel tells the story about the life of Botchan, a teacher, who faces several conflicts. In this novel, there are many cultural terms so that when they are translated, they would trigger some difficulties because some of the terms still do not have equivalences in target language.  The material cultural terms include foods, clothes, houses and their parts, places, and means of transportation. They can be found in the words geisha, kimono, soba, and so on. This research analyzed the equivalence in the translation with the informant as the benchmark to know whether the message in the target text is equivalent with the source text. This method is based on dynamic equivalence concept by Nida and Taber (1974:12). Based on the informant, the methods and techniques used by translator in maintaining the equivalence of message were analyzed. The used theory was the translation methods for cultural terms by Newmark (1988) and translation techniques by Catford (1965) and Hoed (2006).The research showed that the cultural terms were not easy to translate since they were related to the context of culture in the source language. It can be seen from the existing translation data showing two characteristics of equivalent translation that can be achieved through several methods, the understanding of language and culture of source language and target language; the use of suitable translation procedure and technique (transference, cultural equivalence, descriptive translation, transposition, modulation, additional explanation, and standard translation); and the right choice of word based on the intention of the author of novel.